Shaping the Guaraní Territory - Silvetti, Jorge (2015)
The stretch of land in Argentina, Brazil and Paraguay originally occupied by the Guarani is an extended region in the hearth of the River Plate basin, whose environmental characteristics— jungles, impetuous rivers, tropical weather—suffered profound transformations in the last two centuries. Moreover, it is seldom recognized as a unity, traversed as it is by national or provincial borders. As architects, we asked ourselves how one could define this fragment of land as a “territorio.” was the first problem we confronted. To find the answers, we organized a DRCLAS-sponsored international and multidisciplinary workshop, “Territorio Guaraní: Culture, Infrastructure and Natural Resources in the longue durée” in April 2014.